Factors Influencing Performance-Based Budgeting: Leadership Style, Administrative Improvement and Sanctions - Andrian, Elgy; Cris Kuntadi (Dinasti International Journal of Economics, Finance & Accounting, 2022)
Prior research or relevant research is critical in a scientific article. Previous or relevant research strengthens the theory and phenomenon of relationships or influences between variables. This article reviews the factors affecting the preparation of performance-based budgets: leadership style, administrative refinement, and sanctions in a literature study of State Financial Management. This article aims to build a hypothesis of the influence between variables to be used in future research. This literature review article results are 1) leadership style affects Performance-Based Budgeting, 2) Administrative improvement affects the preparation of performance-based budgets, and 3) resources affect performance-based budgeting.